Front Cover: Synthesis, Characterization and Electrochemical Reductive Properties of Complexes [Fe2(CO)4(κ2‐PPh2NR2)(μ‐dithiolato)] Related to the H‐Cluster of [FeFe]‐H2ases (Eur. J. Inorg. Chem. 3/2021). Issue 3 (29th December 2020) - Hobballah, Ahmad; Lounissi, Sondes; Motei, Rachid; Elleouet, Catherine; Pétillon, François Y.; Schollhammer, Philippe
Abstract : The Front Cover shows the fate of protons at a diiron site inspired by the H‐cluster of [FeFe]‐H2 ases. Different conformations favor the capture of protons and their transfer to the diiron core, thus generating a suitable proton channel. Finding the right combinations of ligands for the design of efficient diiron electrocatalysts for proton reduction is like a 3D combination puzzle involving concerted electronic and steric effects through the choice of ligands around the dinuclear site. More information can be found in the Full Paper by C. Elleouet, P. Schollhammer and co‐workers .